Nutritional label use among patients with type 1 diabetes mellitus - CEBECİ, AYBİKE; GÜNEŞ, FATMA ESRA; AKTAÇ, ŞULE (Romanian Society of Diabetes, Nutrition and Metabolic Diseases, 2021)
Background and Aims: In this study, it was aimed to evaluate the nutritional label use of individuals with type 1 DM. Material and Method: This cross-sectional descriptive study was conducted in November 2017 - June 2018. Diabetic individuals were reached through hospitals and social networks. The study was conducted with 105 (64 female, 41 male) individuals with type 1 DM living in Istanbul. A questionnaire about sociodemographic characteristics, biochemical parameters, medical treatment, food label reading status, food label reading reasons were applied in the study. Data were analyzed using SPSS V 16.0 program. Results: 85.7% of the participants read the food label. No significant difference was found when age group and nutritional label reading status were examined (p > 0.05). Besides, information was given to 67.6% of the participants about reading the nutritional label. A significant association was found between nutritional label reading knowledge and carbohydrate counting application and stages (P=0.0001). However, there was no significant difference between biochemical parameters and reading label status (p>0.05). Conclusions: Nutritional label reading should be mentioned more in the medical nutrition therapy and diabetes education. © 2021 The Authors. Romanian Journal of Diabetes, Nutrition and Metabolic Diseases published by Sanatatea Press Group on behalf of the Romanian Society of Diabetes Nutrition and Metabolic Diseases. This is an open access article under the terms of the Creative Commons Attribution License (CC-BY-NC-ND 3.0).
Keywords: Carbohydrate counting; Diabetes education; Nutritional label; Type 1 diabetes